2006
DOI: 10.1007/s10815-005-9001-5
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Y microdeletions in men with testicular cancer and undescended testis

Abstract: Purpose : To investigate a possible association between testicular cancer or undescended testis and Y microdeletions. Methods : It was designed as a retrospective clinical study. A total of 225 men with testicular cancer or undescended testis were included to study. Fertile men (n = 200) were investigated as a control. Genomic DNA, which was extracted from blood samples were investigated with a fluorescent multiplex PCR protocol for screening for Y microdeletions Results : A single STS missing was found in eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…Our study differs from previous studies in that we examined these regions in more detail by using a higher density of markers. Similar to the previous studies in Danish and Norwegian TGCT patients (Frydelund-Larsen et al, 2003;Lutke Holzik et al, 2005;Bor et al, 2006), no large contiguous deletions were demonstrated for any sample in this series in the AZF regions. We did not see the rate of noncontiguous deletions in the AZF regions demonstrated previously for Finnish patients and Argentinean TGCT patients (Bianchi et al, 2002(Bianchi et al, , 2006Richard et al, 2004), suggesting that there is either a difference in the rate of deletion between these populations or that there is some methodological issue giving rise to nonamplification of a PCR product rather that a true deletion of the Y chromosome DNA in these studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study differs from previous studies in that we examined these regions in more detail by using a higher density of markers. Similar to the previous studies in Danish and Norwegian TGCT patients (Frydelund-Larsen et al, 2003;Lutke Holzik et al, 2005;Bor et al, 2006), no large contiguous deletions were demonstrated for any sample in this series in the AZF regions. We did not see the rate of noncontiguous deletions in the AZF regions demonstrated previously for Finnish patients and Argentinean TGCT patients (Bianchi et al, 2002(Bianchi et al, , 2006Richard et al, 2004), suggesting that there is either a difference in the rate of deletion between these populations or that there is some methodological issue giving rise to nonamplification of a PCR product rather that a true deletion of the Y chromosome DNA in these studies.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have examined constitutional DNA from TGCT patients for deletions of the AZF regions on the Y chromosome. A total of 457 TGCT patients were examined and no deletions were identified in the AZF regions (Frydelund-Larsen et al, 2003;Lutke Holzik et al, 2005;Bor et al, 2006). However, the STS markers used for the analysis would not detect the 'gr/gr' deletion.…”
mentioning
confidence: 99%
“…A few studies have focused on Υq11-md specifically in patients with TMD (Cortes et al, 1998;Fagerli et al, 1999;Foresta et al, 1999;Dada et al, 2002b;Suzuki et al, 2002;Kunej et al, 2003;Castro et al, 2004;Ferlin et al, 2004Ferlin et al, , 2005Song et al, 2005;Bor et al, 2006;Giachini et al, 2007;Moretti et al, 2007;Gurbuz et al, 2008). To our knowledge, our study is the largest one published to date (Table 1).…”
Section: Discussionmentioning
confidence: 76%
“…Similarly, another study including 42 adults with normal to severely impaired sperm concentrations and TMD yielded negative results (Fagerli et al, 1999). Similarly, in a study of 64 Danish patients with TMD and abnormal or normal semen analysis, no Yq11-md were detected leading the authors to conclude against an association (Bor et al, 2006). Furthermore, in a small study of 10 selected patients with TMD as a clinical characteristic of Prader-Willi syndrome, Suzuki et al (2002) investigated the possibility that Yq11-md might be associated with the TMD observed in this specific subgroup of patients.…”
Section: Discussionmentioning
confidence: 96%
“…That indeed c-KIT has an important role in the pathogenesis of TGCTs, is supported by deletions (removing all STSs located in a given AZF region) are not associated with TGCT and were not found at all in a total of 575 cancer patients. 37,[39][40][41] Single STS deletions on the Y chromosome are likely to be due to PCR artefacts or to polymorphisms in the primer sequence binding site 41,42 which implies that they must be confirmed by sequencing the deletion breakpoints. Since confirmed single STS deletions have not been described in the literature the appealing link between Y chromosome instability (expressed as mosaic or single STS deletions) and TGCT remains to be established.…”
Section: The Role Of Somatic Genetic Changesmentioning
confidence: 99%